Optical properties of 3rd order Kerr hexagonal nonlinear photonic crystal fiber containing metal - Dixit A.; Tiwari S.; Pandey P.C. (My University, 2025)
This work presents salient features of a new photonic crystal fiber composed of silica in background and coating of gold in holes. This has been done by computing the effective refractive index of semi-vectorial wave propagation equation using the dielectric properties of these materials by finite difference method under analytical boundary condition. The effect of the different filling factor of gold and also the effect of intensity on wave propagation are analyzed respectively with the same adequate physical condition. These results should be useful in obtaining the flattened dispersion with a small effective area in the presence of nonlinearity. © 2017 World Scientific Publishing Company.